KEANEKARAGAMAN BENTUK PERTUMBUHAN KARANG PANTAI TELUK LIMAU DI SUNGAILIAT, KABUPATEN BANGKA - UMROH UMROH (Akuatik: Jurnal Sumberdaya Perairan, 2009)
Coral reefs have functions as the place of biology, chemical and physical globally cycles that has high productivity level. The importance of coral reefs function are to supervise and to protect the ecosystems from activities that lead to damage. Coral reef ecosystem on Bangka Island is in danger because of human activities which could destroy indirectly such as sedimentation caused by tin mining. Sedimentation process can damage to coral reefs and affects on its growth form. Besides of sedimentation, natural factors can affect to corals growth and coral growth form. Under these circumstances, it is necessary to review directly the condition of diversity of coral growth form, especially on the Teluk Limau Shore as efforts to look after of coral reef ecosystems in Bangka Regency in the future. Observation of coral growth forms using Line Intercept Transect Method. Roll meters is being stretched 10 meters long and parallel to the coastline at a depth, but if in one of the depth there is no coral reef, the observation was not done. The results showed coral growth form is more prevalent in the Teluk Limau Coast on transects 1 and 2 are flat / crawl or Coral Encrusting (CE), whereas coral growth form in transect 3 the most dominant is Encrusting Acropora (ACE). Coral growth forms is influenced by hydrodinamis pressure, such as waves or currents, sediment and subareal exposure.